The Implementation of Digital Book Creator Media in Teaching Arabic Speaking Skills - Salsabilah Nur Izzati; Miatin Rachmawati (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2026)
This study aims to describe the implementation of Book Creator, a digital media platform, in teaching Maharah Kalam Arabic to students at Muhammadiyah 4 High School in Jakarta and to determine its contribution to the learning process and outcomes. Using a qualitative descriptive case study approach, descriptive data were obtained through written or oral statements from their participation and behavioral observations. The research subjects were students in class XI IPS 1. Data were obtained through observation, interviews, and documentation, and analyzed using the Miles and Huberman model, which included data reduction, data presentation, and conclusion drawing. The results showed that implementing Book Creator enabled a more interactive and creative learning experience and supported student engagement in the learning process. This media helped students compose dialogues, practice pronunciation, and introduce Arabic vocabulary, while providing space for creativity and collaboration. The discussion shows that Book Creator contributes to the development of speaking skills and strengthens students' cognitive and affective aspects. These findings suggest that this digital media supports more dynamic and flexible Arabic language learning and facilitates various student learning styles through multimedia.